Synthesis, Structure, and Function of Human Adenovirus Small Non-Coding RNAs - Tanel Punga; Mahmoud Darweesh; Göran Akusjärvi (Viruses, 2020)
Human adenoviruses (HAdVs) are common pathogens causing a variety of respiratory, ocular and gastrointestinal diseases. To accomplish their efficient replication, HAdVs take an advantage of viral small non-coding RNAs (sncRNAs), which have multiple roles during the virus lifecycle. Three of the best-characterized HAdV sncRNAs; VA RNA, mivaRNA and MLP-TSS-sRNA will be discussed in the present review. Even though VA RNA has been extensively characterized during the last 60 years, this multifunctional molecule continues to surprise us as more of its structural secrets unfold. Likely, the recent developments on mivaRNA and MLP-TSS-sRNA synthesis and function highlight the importance of these sncRNA in virus replication. Collectively, we will summarize the old and new knowledge about these three viral sncRNAs with focus on their synthesis, structure and functions.